The Role of Gesture in Communication and Cognition: Implications for Understanding and Treating Neurogenic Communication Disorders - Clough, Sharice; Duff, Melissa C. (Frontiers in Human Neuroscience, 2020)
When people talk, they gesture. Gesture is a fundamental component of language that contributes meaningful and unique information to a spoken message and reflects the speaker’s underlying knowledge and experiences. Theoretical perspectives of speech and gesture propose that they share a common conceptual origin and have a tightly integrated relationship, overlapping in time, meaning, and function to enrich the communicative context. We review a robust literature from the field of psychology documenting the benefits of gesture for communication for both speakers and listeners, as well as its important cognitive functions for organizing spoken language, and facilitating problem-solving, learning, and memory. Despite this evidence, gesture has been relatively understudied in populations with neurogenic communication disorders. While few studies have examined the rehabilitative potential of gesture in these populations, others have ignored gesture entirely or even discouraged its use. We review the literature characterizing gesture production and its role in intervention for people with aphasia, as well as describe the much sparser literature on gesture in cognitive communication disorders including right hemisphere damage, traumatic brain injury, and Alzheimer’s disease. The neuroanatomical and behavioral profiles of these patient populations provide a unique opportunity to test theories of the relationship of speech and gesture and advance our understanding of their neural correlates. This review highlights several gaps in the field of communication disorders which may serve as a bridge for applying the psychological literature of gesture to the study of language disorders. Such future work would benefit from considering theoretical perspectives of gesture and using more rigorous and quantitative empirical methods in its approaches. We discuss implications for leveraging gesture to explore its untapped potential in understanding and rehabilitating neurogenic communication disorders.